Acompanhamento do processo produtivo e controle de qualidade de dermatos na farmacia Nova Phórmula - Almeida, Alana Helen Batista de (Universidade Federal Rural do Semi-Árido, 2017)
Report prepared during the supervised internship period in the pharmacy company New Phórmula with the purpose of presenting the activities developed in it. The New Phórmula is a medium-sized company located in the municipality of Pau dos Ferros, RN. The pharmacies of magistrais have the differential of offering a customized product meeting the need of each customer, following the regulation of ANVISA, was done in the laboratory of liquid and semisolids of the pharmacy New Phórmula, a capillary lotion to stimulate the growth and to stop the fall of Hair and used the organoleptic and pH analyzes to attest to the quality of this product. Other analyzes were proposed for greater quality control of the goods, with the intention of guaranteeing greater customer satisfaction
Monografia
Keywords: Manipulados; Nova Phórmula; Controle de qualidade; Dermato; Cosméticos; Manipulated; New Phormula; Quality control; Dermatology; Cosmetics; ENGENHARIAS::ENGENHARIA QUIMICA